Bolsa Família program and incomplete childhood vaccination in two Brazilian cohorts - Francelena de Sousa Silva; Rejane Christine de Sousa Queiroz; Maria dos Remédios Freitas Carvalho Branco; Vanda Maria Ferreira Simões; Yonna Costa Barbosa; Marcelo Augusto Ferraz Ruas do Amaral Rodrigues; Marco Antonio Barbieri; Heloísa Bettiol; Maria da Conceição Pereira Saraiva; Luiz Guilherme Scorzafave; Maria Isabel Accoroni Theodoro Habenschus; Antônio Augusto Moura da Silva (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To estimate the effect of being a beneficiary of the Bolsa Família Program (BFP) in the vaccination of children aged 13 to 35 months. METHODS: Our study was based on all birth records of residents of Ribeirão Preto (SP) and probabilistic sampling with 1/3 of the births of residents of São Luís (MA), selecting low-income children, born in 2010, belonging to the cohorts Brazilian Ribeirão Preto and São Luís Birth Cohort Studies and eligible for the Bolsa Família program. The information of Cadastro Único (CadÚnico - Single Registry) was used to categorize the receipt of benefit from the BFP (yes or no). The final sample consisted of 532 children in Ribeirão Preto and 1,229 in São Luís. The outcome variable was a childhood vaccine regimen, constructed with BCG, tetravalent, triple viral, hepatitis B, poliomyelitis, rotavirus and yellow fever vaccines. The adjustment variables were: economic class, mother's schooling and mother's skin color. Children with monthly per capita family income of up to R$ 280.00 and/or economic class D/E were considered eligible for the benefit of the BFP. A theoretical model was constructed using a directed acyclic graph to estimate the effect of being a beneficiary of the BFP in the vaccination of low-income children. In the statistical analyses, weighing was used by the inverse of the probability of exposure and pairing by propensity score. RESULTS: Considering a monthly per capita family income of up to R$ 280.00, being a beneficiary of the BFP had no effect on the childhood vaccination schedule, according to weighing by the inverse of the probability of exposure (SL-coefficient: −0.01; 95%CI −0.07 to 0.04; p = 0.725 and RP-coefficient: 0.04; 95%CI −0.02 to 0.10; p = 0.244) and pairing by propensity score (SL-coefficient: −0.01; 95%CI −0.07 to 0.05; p = 0.744 and RP-coefficient: 0.04; 95%CI −0.02 to 0.10; p = 0.231). CONCLUSIONS: The receipt of the benefit of the BFP did not influence childhood vaccination, which is one of the conditionalities of the program. This may indicate that this conditionality is not being adequately monitored.